Role of virtual modules to supplement neurosurgery education during COVID-19. (September 2021) - Singh, Ramandeep; Baby, Britty; Singh, Rajdeep; Suri, Ashish
Highlights: The Covid-19 pandemic adversely affected the surgical education of residents. Both trainees and faculty need to follow physical distancing and shift rearrangements. Residents had fewer chances to visit surgical training labs and operating rooms. Virtual modules to supplement the neurosurgery education program have been developed. It included neuro-anatomy, neurosurgical procedures, instrumentation, and planning modules. Modules were virtually demonstrated to resident neurosurgeons through Cisco Webex. Virtual modules were found to be an effective method to supplement neurosurgery education. Abstract: The advent of the COVID-19 pandemic has disrupted all aspects of neurosurgery education, and it is now challenging to conduct routine sessions. Maintenance of essential standard education among novice neurosurgeons during the pandemic is of paramount importance. The aim of this study was the development of virtual modules and validation of its role to supplement the neurosurgery education program. We developed the virtual modules relevant to neuro-anatomy, neurosurgical procedures, instrumentation, and neurosurgical planning. These modules were virtually demonstrated to twenty-seven resident neurosurgeons through Cisco Webex online platform. They provided their rating on the aptness of virtual modules for different neurosurgery applications on various parameters using 10 points Likert scale. The parameters included quality, learning, confidence building capacity, usefulness, and overall satisfaction. The results obtained for each module were analysed and the average score was used for the comparison. The highest rating on quality was obtained by the neurosurgical instrumentation module. The highest rating for learning and confidence building capacity was given to neurosurgical procedure animation. The usefulness and overall satisfaction were highly rated for neurosurgical planning module. The results show that developed virtual modules provide an effective method to supplement the neurosurgery education program in the current scenario involving physical distancing and shift rearrangements. These virtual modules help in limiting the visits to operation room, anatomy and surgical training labs, and allow residents to learn online at their pace.